Penilaian Tingkat Kerusakan Pantai Di Kecamatan Leitimur Selatan Dan Prioritas Penanganannya - Paulinus Marselo Rumlus; Warniyati Warniyati; Tri Octaviani Sihombing (CV. Ulil Albab Corp, 2026)
South Leitimur District is one of the coastal areas in Ambon City, with a landscape consisting of mountains, hills, and a fairly long coastline. The coastal area in South Leitimur District has experienced coastal damage, such as abrasion, damage to coastal protection structures, and a decline in the quality of the coastal environment. One real-life case that has been highlighted is the damage to the embankment in Hutumuri Village due to prolonged abrasion and increasing sea wave intensity. This study aims to assess the level of coastal damage that has occurred in South Leitimur District and determine the priority scale for its handling based on the severity of the damage and the level of regional importance. The method used refers to the guidelines of the Circular Letter of the Minister of Public Works No. 08/SE/M/2010. The assessment was conducted in five villages: Hutumuri, Rutong, Leahari, Hukurila, and Kilang. Each coastal segment was analyzed using the EA-2 benchmark (damage to coastal structures), taking into account visual aspects in the field, photo documentation, and GPS coordinates. The results showed that most coastal segments experienced levels of damage ranging from light to very severe. The segments with the highest damage were segments 4b and 7b in Hutumuri Village, and Segment 1b in Kilang Village, with a damage score of 200, which falls into the priority category C (Preferred). This situation indicates an urgent need for coastal protection measures and rehabilitation. Furthermore, the weighting calculation also takes into account the importance of the area, such as the presence of dense settlements, main road access, and economic activity in the surrounding community.